The Marketplace Variables in Successful and Unsuccessful NPD Projects in Technology Intensive Companies - Matti J. Haverila (Journal of Technology Management & Innovation, 2010)
We present an exploratory investigation of how managers conceptualize and perceive ‘marketplace’ variables in successful and unsuccessful New Product Development (NPD) projects, and explore the role that marketplace variables play in differentiating between successful and unsuccessful NPD outcomes. Limitations and future research directions are also discussed. Our findings indicate that managers perceive the marketplace in multiple ways during the NPD process and also that differences exist in metric equivalence across successful and unsuccessful NPD projects. Also, although half of the marketplace variables are positively related to NPD success, managers in Finnish technology companies appear to attach higher relative importance to market attractiveness rather than market competitiveness variables. Marketplace variables appear to be less important than in the Korean and Chinese samples, and much more important than  in the Canadian sample in the Mishra et all study (1996), and similarly much more important than in the Cooper study (1979b).